Diagnostic modeling of dimethylsulfide production in coastal water west of the Antarctic Peninsula - Herrmann, Maria; Najjar, R.G.; Neeley, Aimee R.; Vila-Costa, Maria; Dacey, J.W.H.; DiTullio, G.R.; Kieber, David J.; Kiene, Ronald P.; Matrai, Patricia; Simó, Rafel; Vernet, Maria (Continental Shelf Research, 2012)
14 pages, 10 figures, 3 tables The rate of gross biological dimethylsulfide (DMS) production at two coastal sites west of the Antarctic Peninsula, off Anvers Island, near Palmer Station, was estimated using a diagnostic approach that combined field measurements from 1 January 2006 through 1 March 2006 and a one-dimensional physical model of ocean mixing. The average DMS production rate in the upper water column (0–60 m) was estimated to be 3.1±0.6 nM d−1 at station B (closer to shore) and 2.7±0.6 nM d−1 at station E (further from shore). The estimated DMS replacement time was on the order of 1 d at both stations. DMS production was greater in the mixed layer than it was below the mixed layer. The average DMS production normalized to chlorophyll was 0.5±0.1 (nM d−1)/(mg m−3) at station B and 0.7±0.2 (nM d−1)/(mg m−3) at station E. When the diagnosed production rates were normalized to the observed concentrations of total dimethylsulfoniopropionate (DMSPt, the biogenic precursor of DMS), we found a remarkable similarity between our estimates at stations B and E (0.06±0.02 and 0.04±0.01 (nM DMS d−1)/(nM DMSP), respectively) and the results obtained in a previous study from a contrasting biogeochemical environment in the North Atlantic subtropical gyre (0.047±0.006 and 0.087±0.014 (nM DMS d−1)/(nM DMSP) in a cyclonic and anticyclonic eddy, respectively). We propose that gross biological DMS production normalized to DMSPt might be relatively independent of the biogeochemical environment, and place our average estimate at 0.06±0.01 (nM DMS d−1)/(nM DMSPt). The significance of this finding is that it can provide a means to use DMSPt measurements to extrapolate gross biological DMS production, which is extremely difficult to measure experimentally under realistic in situ conditions. This research was supported by the National Science Foundation (NSF) Office of Polar Programs (OPP) under Grant OPP-0083078 to P.A. Matrai. Data from the Palmer LTER data archive were supported by NSF Grant OPP-0217282. Meteorological ...